(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Introduction. Osteoid osteoma represents about 3% of all primary bone tumors and 11% of all benign bone tumors. Data from the literature suggest that a neuromuscular rehabilitation program after osteoid osteoma surgery is very beneficial and improves the general quality of life. Material and methods. A 30-year-old male patient with intermittent right shoulder pain radiating to the right hand, and recurrent myalgias in the past year presented to our neurological department. The neurological examination highlighted limitation of the abduction of the right upper limb. The paraclinical investigations included plain radiography of the right upper limb and electroneurography, which were normal, and native cervical MRI which revealed discrete C5 disc overflow, without visible signs of compression. The patient presented limited initial response to NSAIDs, so his treatment was changed to corticosteroid therapy. Further, the patient was guided to undergo a rheumatological examination where a musculoskeletal ultrasound was performed, showing no any specific modification. Additionally, we indicated a native right shoulder MRI, which revealed a signal modification of the proximal humeral diaphysis. We further indicated an MRI scan with contrast of the upper right limb, which revealed a nidus at the top one-third of the humerus. Additionally, a CT scan with contrast of the same region displayed images that were highly suggestive of osteoma. The patient was referred to the orthopedics department, where a complete resection of the tumor was performed, and the pathology report confirmed the final diagnosis of osteoid osteoma. Conclusions. Recovery after osteoid osteoma surgery is more beneficial if the neuromuscular rehabilitation program, that has an important role in increasing muscle strength, is combined with orthopedic devices and pain medication. Keywords: bone tumor, osteoid osteoma, upper limb, imaging changes, differential diagnosis difficulty